The somatotropic axis in short children born small for gestational age: relation to insulin resistance. - Woods, K; van Helvoirt, M; Ong, K; Mohn, A; Levy, J; de Zegher, F; Dunger, D (2002)
To determine whether hyperinsulinemia and reduced insulin sensitivity in individuals born small for gestational age (SGA) could be related to persisting abnormalities of the GH/IGF-I axis, we assessed overnight GH secretory profiles and measured fasting glucose, insulin, intact and 32,33 split proinsulin, and IGF-I levels in 16 short SGA children (age range 2.3-8.0 y) and in controls. Insulin sensitivity was calculated using the homeostasis model. Compared with short normal-birthweight controls (n = 7, age range 2.3-5.0 y), short SGA children had higher fasting insulin levels (means: 26.8 vs 20.6 pmol/L, p = 0.02), lower insulin sensitivity [means: 204 vs 284 %homeostasis model assessment (HOMA), p = 0.01], and higher beta cell function (112 vs 89 %HOMA, p = 0.04). SGA children also had lower levels of IGFBP-1 (87.0 vs 133.8, p = 0.04), but similar IGF-I levels (IGF-I SDS: -1.1 vs -1.7, p = 0.4). Compared with normal-height controls (n = 15, age range 5.6-12.1 y), SGA children had higher overnight GH secretion (GH maximum: 55.9 vs 39.6 mU/L, p = 0.01; mean: 13.1 vs 8.9, p = 0.004; minimum: 1.2 vs 0.6, p = 0.02). Interestingly, among SGA children, fasting insulin levels and insulin sensitivity were significantly related to overnight GH secretion (insulin sensitivity vs maximum GH: r = -0.68, p = 0.01; vs GH pulse amplitude r = -0.71, p = 0.007). The only hormone level significantly related to current height velocity was C-peptide (r = 0.75, p = 0.008). In conclusion, elevated fasting insulin levels and reduced insulin sensitivity in short SGA children was related to elevated levels of overnight GH secretion. We hypothesize that resistance to the somatotropic actions of GH and IGF-I in short SGA children may contribute directly to reduced insulin sensitivity.